The Role of Microbiota in Atopic Dermatitis - Desiana Widityaning Sari; Nur Annisa Nugraheningtyasari (Journal of Medicine and Health Technology, 2025)
Skin microbiota play an important role in the pathogenesis of AD. Damage to the integrity of the skin mucosa allows penetration of allergens and colonization of the skin by pathogenic microorganisms. This can then stimulate inflammation related to excessive activation of Th2 lymphocytes throughout the body including the digestive tract and respiratory tract. The understanding of the latest definition of AD emphasizes this disease as a chronic inflammatory disease characterized by disruption of the skin barrier, inflammation, and dysbiosis (an imbalance between commensal and pathogenic bacteria, which then has significant health implications). Skin dysbiosis is based on an increase in the concentration of Staphylococcus aureus colonization, which causes a decrease in the number of commensal bacteria. Changes in the microbiota in AD affect the functioning of the immune system, stimulating inflammatory reactions that are manifested as atopic eczema. This concept of dysbiosis is important to discuss because it can influence new strategies for the treatment and prevention of AD. This article will further discuss the role of microbiota in AD.